Improved method for settlement prediction of shallow foundations on sand. Issue 6 (11th December 2020) - Berardi, Riccardo; Cambiaggi, Ludovica
Abstract : Shallow foundations on sands are typically designed with reference to settlements that are difficult to predict with a high level of accuracy. The main uncertainties originate from the soil's non-linear behaviour and the fact that methods currently adopted in practice rely on linear elastic approaches and empirical correlations between soil stiffness and in situ test results. To improve the prediction of foundation settlement it is necessary to account for the dependence of stiffness on soil density, stress state and strain levels – even in relatively simple methods. The main objective of this paper is to provide a contribution in this field. An already formulated elastic approach is revised and modified in order to improve the assessment of soil stiffness, taking into account non-linearity due to strain levels and mechanical non-homogeneity, through definition of an 'active zone' that is more consistent with the geometry and size of the foundation. A comparison of calculated and measured settlements demonstrates the feasibility of the proposed non-linear method for both small and large deformation levels.